Stakeholder-driven transformative adaptation is needed for climate-smart nutrition security in sub-Saharan Africa - Jennings, Stewart; Challinor, Andrew J.; Smith, Pete; Macdiarmid, Jennie I.; Pope, Edward; Chapman, Sarah; Bradshaw, Catherine; Clark, Heather; Vetter, Sylvia; Fitton, Nuala; King, Richard; Mwamakamba, Sithembile; et al. (Springer, 2024)
Abstract Improving nutrition security in sub-Saharan Africa under increasing climate risks and population growth requires a strong and contextualized evidence base. Yet, to date, few studies have assessed climate-smart agriculture and nutrition security simultaneously. Here we use an integrated assessment framework (iFEED) to explore stakeholder-driven scenarios of food system transformation towards climate-smart nutrition security in Malawi, South Africa, Tanzania and Zambia. iFEED translates climate–food–emissions modelling into policy-relevant information using model output implication statements. Results show that diversifying agricultural production towards more micronutrient-rich foods is necessary to achieve an adequate population-level nutrient supply by mid-century. Agricultural areas must expand unless unprecedented rapid yield improvements are achieved. While these transformations are challenging to accomplish and often associated with increased greenhouse gas emissions, the alternative for a nutrition-secure future is to rely increasingly on imports, which would outsource emissions and be economically and politically challenging given the large import increases required.